The Symbolic Significance of Digital Services Tax and its Practical Consequences - Rigó, Csaba Balázs; Tóth, András (Public Finance Quarterly, 2020)
Global companies providing digital services utilise the public services of the countries from which they derive their revenue generating datasets. Despite this, they do not necessarily contribute to supporting public burden in these countries. The present study aims to demonstrate the importance of digital services taxation not only in terms of increasing tax revenue, but also in terms of symbolic significance. It is argued that global digital companies should provide a fair contribution, in the form of a percentage of the revenue generated from the use of citizens’ data, to those countries from which these data are derived. In other words, states should also receive a fair share of the exploitation of what can be considered as the “new oil”, namely data. After analysing the political and legal environment and reviewing theories of state philosophy, the authors conclude that the success of joint action at EU level on this symbolic issue is highly questionable and therefore action at level of individual Member States may be needed.